2015
DOI: 10.1016/j.schres.2015.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Pursuit eye movements as an intermediate phenotype across psychotic disorders: Evidence from the B-SNIP study

Abstract: Smooth pursuit eye tracking deficits are a promising intermediate phenotype for schizophrenia and possibly for psychotic disorders more broadly. The Bipolar-Schizophrenia Network on Intermediate Phenotypes (B-SNIP) consortium investigated the severity and familiality of different pursuit parameters across psychotic disorders. Probands with schizophrenia (N=265), schizoaffective disorder (N=178), psychotic bipolar disorder (N=231), their first-degree relatives (N=306, N=217, N=273, respectively) and healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 55 publications
5
55
1
Order By: Relevance
“…There have been many studies on the effect of antipsychotics on smooth pursuit, and the results vary. A recently published multisite study reported no significant association between smooth pursuit measures and antipsychotic use . Studies on antipsychotic‐naïve patients with schizophrenia have also shown smooth pursuit abnormalities before treatment initiation as well .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies on the effect of antipsychotics on smooth pursuit, and the results vary. A recently published multisite study reported no significant association between smooth pursuit measures and antipsychotic use . Studies on antipsychotic‐naïve patients with schizophrenia have also shown smooth pursuit abnormalities before treatment initiation as well .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of eye movement abnormalities in schizophrenia have shown a significant decline in saccade control and smooth pursuit eye movement, and studies integrating genetics and brain function add knowledge to the underlying cause of these abnormalities . Studies using single eye movement measures as neurophysiological biomarkers have been conducted, showing specific findings in schizophrenia compared to mood disorders . There are also studies that use multiple eye movement measures to classify patients with schizophrenia and healthy controls, resulting in a discriminative accuracy of 80–90% .…”
mentioning
confidence: 99%
“…In example plots of the eye positions during smooth pursuit, healthy participants smoothly follow the visual target (Figure A). However, in the participants with schizophrenia, the position of the eye often lags behind the target (especially in the horizontal direction) because the speed of eye movements tends not to keep up with the speed of the moving visual target, and catch‐up saccades are seen immediately afterward (Figure B). Studies have also shown the possibility that genetic factors are associated with smooth pursuit eye movement characteristics in schizophrenia …”
Section: Eye Movement Characteristics In Schizophreniamentioning
confidence: 99%
“…The Bipolar‐Schizophrenia Network on Intermediate Phenotypes (B‐SNIPS) Consortium was formed to examine intermediate phenotypes involving smooth pursuit eye movement measures and saccade control measures across psychotic disorders including schizophrenia, schizoaffective disorder, and bipolar disorder with psychotic symptoms . Their study included more than 1000 participants and showed that impairments of smooth pursuit were larger in participants with schizophrenia than participants with the other disorders . In Japan, the Cognitive Genetics Collaborative Research Organization (COCORO) consortium (Figure ) has recently been organized, and multicenter eye movement research is currently running within this framework.…”
Section: Current Problems and The Establishment Of Large‐scale Multicmentioning
confidence: 99%
See 1 more Smart Citation